Construction of Diagnostic Tests to Diagnose the Misconceptions of Junior High School Students on Dynamic Electrical Materials - Ika, Novrina; Ahmad Tarmizi Abdul, Karim; Andri Estining, Sejati (Journal of Teaching and Education, 2022)
Misconceptions in physics learning, particularly in dynamic electricity, often hinder students’ conceptual understanding and problem-solving abilities. This study aimed (1) to develop a valid and reliable three-tier diagnostic test and (2) to identify junior high school students’ misconceptions regarding dynamic electricity concepts. The research employed a Research and Development (RD) approach adapted from the Borg and Gall model and modified according to Treagust’s diagnostic test development framework. The development process involved content determination, information gathering, test construction, expert validation, and field testing. The instrument consisted of three-tier multiple-choice items comprising answer selection, reasoning, and confidence level. Item validity was analyzed using the point-biserial correlation coefficient, while reliability was calculated using the Kuder–Richardson Formula 20 (KR-20). The finalized instrument included 21 valid items with a reliability coefficient of 0.75, indicating good reliability. The diagnostic test was administered to 189 students from five classes at a public senior high school. The findings revealed that 49.4% of students experienced misconceptions, 36.6% understood the concepts, 6.9% had weak conceptual understanding, 5.6% did not understand the concepts, and 1.1% answered correctly by guessing. These results indicate that misconceptions in dynamic electricity remain prevalent and highlight the importance of diagnostic assessment as a basis for remedial instruction.